Two Dimensional Proteomic Analyses Revealed Salinity and Drought Tolerance Related Protein Alterations in Two Gamma-Induced Soybean Mutants - AYAN, ALP; MERİÇ, SİNAN; GÜMÜŞ, TAMER; ÇELİK, ÖZGE; ATAK, ÇİMEN (Julius Kuhn-Institut Federal Research Center for Cultivated Plants, 2025)
Soybean [Glycine max (L.) Merr], is an important industrial oil seed plant. Along with the nutritional value for humans and animals, it has raw materials for various industrial products. In the present study, we investigated the two-dimensional protein expression profiles in salinity and drought tolerant mutant plants derived from S04-05 soybean variety by Cs-137 gamma radiation source induced mutations. Altogether 54 different protein spot alterations were identified as salinity and drought responsive by two-dimensional electrophoresis and MALDI-TOF-MS. A protein-protein interaction network was constructed considering significantly altered proteins by STRING analysis software. Identified proteins, which presented differential expressions under both stress conditions, were clustered under 13 distinct groups based on their cellular functions. Two of these biological processes, photosynthesis and carbohydrate metabolism, were found significantly altered by KEGG analysis. Our results contribute proteomic data to salinity and drought tolerance of our soybean mutants, which originated from S04-05, a variety mildly susceptible to salinity and drought. These results may provide a basis for future investigations into the genetic and physiological aspects of both stress tolerances.
Keywords: Drought Tolerance; Glycine Max (L.) Merr; Mutation Breeding; Proteomics; Cs-137; Salinity Tolerance